EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING BERBANTUAN YOUTUBE UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS PIDATO SISWA KELAS VIII SMP NEGERI 8 CIBITUNG - Diana, Lala; Hartati, Dian; Pratiw, Wienike Dinar; Nurfadilah, Kurnia Dewi (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This study aims to determine the differences in students' speech writing skills before and after using the YouTube-assisted experiential learning model and to analyze the effectiveness of the application of the model in improving the speech writing skills of class VIII students of SMP Negeri 8 Cibitung. The study used a quantitative approach with a quasi-experimental method and a non- equivalent control group design. The sample consisted of 80 students divided into two classes, namely the control class (using the blended learning model) and the experimental class (using the YouTube-assisted experiential learning model). Data collection was carried out through observation, questionnaires, documentation, and tests. Data analysis techniques include normality, homogeneity, N-Gain, and t-test tests using SPSS version 30.0. The results showed that the average posttest score of students in the experimental class (86.5) was higher than the control class (73.8). The N-Gain value in the experimental class was 0.72 (quite effective category) while the control class was 0.39 (ineffective category). The results of the t-test showed a significant difference between the two (sig. <0.01). In addition, the results of the questionnaire showed an increase in students' positive perceptions of learning. Thus, the YouTube-assisted experiential learning model has proven to be effective compared to the blended learning model in improving the ability to write speech texts of class VIII students of SMP Negeri 8 Cibitungm.